2020
DOI: 10.1159/000510135
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a New Score to Assess Surgical Efficiency in Holmium Laser Enucleation of the Prostate

Abstract: Introduction: While holmium laser enucleation of the prostate (HoLEP) is accepted as safe and efficient, a long learning curve is considered the main reason for its slow adoption in clinical practice. So far, no standardized and easy-to-use parameter has been implemented to measure surgical experience or efficiency which could be useful for training and quality control purposes. The aim of the present study was to evaluate the learning curves of 2 HoLEP beginners and to identify applicable efficiency outcome m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…This is worrisome as a low complication rate should be the utmost goal for every intervention, especially for a surgery, which is conducted for a benign disease. Rosenhammer et al [25] found that ASA status and prostate cancer were independent predictors for grade ≥ 2 complications but not the caseload, which is consistent with our results, where we also found ASA status and prostate volume, but not caseload, as significant predictor of major complications. Moreover, Westhofen et al [22] found the overall incidence of treatment-related adverse events was significantly higher without a training program.…”
Section: Discussionsupporting
confidence: 93%
“…This is worrisome as a low complication rate should be the utmost goal for every intervention, especially for a surgery, which is conducted for a benign disease. Rosenhammer et al [25] found that ASA status and prostate cancer were independent predictors for grade ≥ 2 complications but not the caseload, which is consistent with our results, where we also found ASA status and prostate volume, but not caseload, as significant predictor of major complications. Moreover, Westhofen et al [22] found the overall incidence of treatment-related adverse events was significantly higher without a training program.…”
Section: Discussionsupporting
confidence: 93%
“…Prostate-specific antigen (PSA) assessment, digital-rectal examination (DRE), and rebiopsies are performed frequently in order to switch to an invasive treatment when signs of progression appear [7,8]. However, due to the low detection rate of 4-9% of prostate cancer after surgical BPO treatment [9][10][11][12][13], data on oncological outcomes of IPC patients are scarce, especially of those managed with AS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by imaging methods such as endorectal MRI after a biopsy that alterations in the prostatic tissue can last up to 21 days [15,16] and in some cases up to 4.5 months [17]. Besides, Rosenhammer et al [18] demonstrated that patients with known or expected prostate cancer may be more complex cases with a higher risk for complications. In our study, HoLEP was performed 7-21 days after the biopsy in all patients in group 1.…”
Section: Discussionmentioning
confidence: 99%